Therapeutic Targeting of Histone Modifications in Adult and Pediatric High-Grade Glioma - Williams, Maria J.; Singleton, Will G. B.; Lowis, Stephen P.; Malik, Karim; Kurian, Kathreena M. (Frontiers in Oncology, 2017)
Recent exciting work partly through The Cancer Genome Atlas has implicated epigenetic mechanisms including histone modifications in the development of both pediatric and adult high-grade glioma (HGG). Histone lysine methylation has emerged as an important player in regulating gene expression and chromatin function. Lysine (K) 27 (K27) is a critical residue in all seven histone 3 variants and the subject of posttranslational histone modifications, as it can be both methylated and acetylated. In pediatric HGG, two critical single-point mutations occur in the H3F3A gene encoding the regulatory histone variant H3.3. These mutations occur at lysine (K) 27 (K27M) and glycine (G) 34 (G34R/V), both of which are involved with key regulatory posttranscriptional modifications. Therefore, these mutations effect gene expression, cell differentiation, and telomere maintenance. In recent years, alterations in histone acetylation have provided novel opportunities to explore new pharmacological targeting, with histone deacetylase (HDAC) overexpression reported in high-grade, late-stage proliferative tumors. HDAC inhibitors have shown promising therapeutic potential in many malignancies. This review focuses on the epigenetic mechanisms propagating pediatric and adult HGGs, as well as summarizing the current advances in clinical trials using HDAC inhibitors.